The law and practice of banking : volume 1: Banker and customers - Holden, J. Milnes (London : Pitman Publishing, 1982)
This third edition of Volume 1, sets out the relationship between the banker and customer, quoting recent legal decisions statutes that affect bankers.
Includes index.
eej 20/08/2019
Loans
Keywords: Banking law; Banks and banking; Bankers and customers; Great Britain